Novel robotic TCD ultrasound with bubbles versus standard care to detect right to left shunt: Study methods. Issue 5 (3rd June 2021) - Rubin, Mark N.; Alexandrov, Andrei V.; Douville, Colleen; Rinsky, Brenda; Tsivgoulis, Georgios
ABSTRACT: Background and Purpose: Right to left shunt (RLS), from patent foramen ovale (PFO) or elsewhere, is a recognized risk factor for stroke. Current standard of care for RLS diagnosis includes transthoracic echocardiography (TTE) which is insensitive, transesophageal echocardiography (TEE) which is invasive, and transcranial Doppler (TCD) which has excellent sensitivity and specificity for RLS but is heavily operator dependent and expertise is scarce. The purpose of this study was to evaluate the RLS detection rate of a novel robotic‐assisted TCD (ra‐TCD) to standard of care diagnostic techniques, including TTE, TEE, and TCD. Methods: This is a multicenter, prospective, single‐arm, nonsignificant risk device study of ra‐TCD versus TTE for RLS diagnosis in adult patients who present with neurological signs and symptoms that include embolic stroke or transient ischemic attack on the differential diagnosis. Up to 150 subjects will be enrolled at up to seven centers considering the prevalence of PFO, suboptimal transtemporal windows, and potential dropouts. Enrolled patients will undergo ra‐TCD supine and at 45° in a manner otherwise in line with standard of care TCD bubble technique. The enrolled patients will have undergone TTE, and optionally standard TCD and TEE, per usual care. Results: The primary efficacy endpoint is percent detection of RLS by ra‐TCD compared against TTE. The primary safety endpoint is the incidence of device‐related serious adverse events. Conclusions: This is the first multicenter, prospective study evaluating the accuracy, feasibility, and safety of novel ra‐TCD for the diagnosis of RLS as compared to standard of care diagnostics.